Characterization of bacterial communities of ewe’s vaginal tract and its potential impact on reproductive efficiency - E. L. Reinoso-Peláez; F. Puente-Sánchez; M. Serrano; J. H. Calvo; M. Ramón; M. Saura (Animal Microbiome)
Abstract The success rate of artificial insemination in sheep remains suboptimal, which has led to an emerging interest in the impact of the reproductive tract microbiome on this process. This research aims to identify the ewes’ vaginal core bacterial community, examine the factors influencing bacterial composition, and to determine the association between vaginal bacteria and pregnancy success. By using a robust dataset comprising 331 multiparous ewes from three Spanish breeds (Latxa, Manchega, Rasa Aragonesa) across four herds, this study performed the sequencing of the hypervariable regions V3-V4 of the 16S ribosomal RNA gene and the identification of Amplicon Sequence Variants (ASV) to analyze the bacterial community. Our analysis revealed a core bacterial primarily consisting of the genera Streptobacillus, Histophilus, Fusobacterium, Oceanivirga, and Parvimonas. Alpha and beta diversity, as well as Random Forest analysis, identified that herd and breed were the main drivers of bacterial variability. PERMANOVA analysis also showed significant differences in bacterial composition and abundance associated with pregnancy outcomes. Notably, specific ASVs associated with Fusobacterium, Leptotrichia, Histophilus, Escherichia, and Bacteroides were predominantly found in non-pregnant ewes, while genera such as Pseudomonas, Acinetobacter, and Brevundimonas were more abundant in pregnant ewes. This study contributes to the knowledge about the critical roles of specific bacteria in determining reproductive success in sheep and provides novel insights about the importance of different factors involved in the composition of ewes’ vaginal bacterial communities.